Problem-Based Learning Model On Students’ Mathematical Ability: A Meta-Analysis - Yadi Mulyadi; Iva Sarifah; Mahmud Yunus (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Mathematical ability is a core competence that students must master and develop in mathematics education. One instructional model considered effective for enhancing this competence is Problem-Based Learning (PBL), which positions students at the center of learning by engaging them in solving contextual and meaningful problems. Through these activities, students are encouraged to strengthen key mathematical skills, including conceptual understanding, reasoning, and problem-solving. This study aims to comprehensively analyze the impact of the PBL model on students’ mathematical abilities in Indonesia through a meta-analytic approach. A total of 30 studies were systematically reviewed following PRISMA guidelines. Data analysis was conducted using JASP to calculate the pooled effect size, the heterogeneity level, the forest plot, the funnel plot, and the potential publication bias. The meta-analysis produced a summary effect size of 1.132 (95% confidence interval: 0.873–1.390), indicating a large effect. The heterogeneity index (I²=83.26%) showed substantial differences across studies; therefore, a random-effects model was employed. Although the funnel plot showed slight asymmetry, the Fail-Safe N value of 9.29>1 indicated that publication bias did not substantially affect the results. Overall, the findings confirm that PBL has a significant and consistent positive effect on students’ mathematical abilities across various educational levels in Indonesia.